Fenomena Curhat Secara Anonim di Akun Menfess Twitter (Studi Etnografi Virtual Pada Akun @collegemenfess) - Ayu Febryani; Ade Liza Maulitaya (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2023)
This study aims to describe the background, the reasons for choosing to confide in the @collegemenfess menfess account, and describe the benefits that are obtained after confiding in the menfess @collegemenfess account. This research was conducted using qualitative research with a virtual ethnographic approach. The data collection technique used was observation, interviews, and documentation. The data analysis technique used in this study is the Cyber Media Analysis (AMS) technique. The results of this study explain that someone's background sends messages/confinees at @collegemenfeess because of their anonymous status which allows them to reveal their true identity. With this anonymous status, message senders are free to express opinions and express themselves. So that the benefits obtained are the satisfaction felt by the sender of the message because he can issue his complaints and also get the information he wants.